Evidence that blockade of post-synaptic 5-HT1 receptors elicits feeding in satiated rats. - Dourish, C; Clark, M; Fletcher, A; Iversen, S (1989)
The effects of nine central 5-HT antagonists on food intake in free feeding male rats were examined. The 5-HT2 antagonists ritanserin and ketanserin and the selective 5-HT3 antagonists ICS 205-930 and MDL 72222 had no effect on food intake. In contrast, the non-selective 5-HT antagonists metergoline, methiothepin, mesulergine, mianserin and methysergide (all of which have high affinity for various 5-HT1 receptor subtypes), dose-dependently increased food intake during a 4-h daytime test. Furthermore, metergoline dose dependently increased food intake over a 24-h period. Surprisingly, mesulergine decreased food intake over a 24-h period at the same doses that increased daytime food intake. This may indicate that the increase in daytime feeding produced by mesulergine is a non-specific response. Although the antagonists used have varying degrees of selectivity for 5-HT receptor subtypes, the pattern of results suggests that postsynaptic 5-HT1 receptors (possibly of the 5-HT1C type) play an important role in the control of feeding in rats.